Highly elastic waterproof skin-feeling tablecloth based on flexible polymer and preparation method thereof
By adding silicone modifiers, antistatic fillers, light stabilizers and flexible plasticizers to the polyurethane materials, the problem of hard hand and insufficient waterproofness of polyurethane materials is solved, and a tablecloth product with high elasticity, waterproof, antistatic and durability is achieved, maintaining a soft touch.
Patent Information
- Application Number
- CN202411631441.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
In the prior art, when polyurethane materials improve water resistance and durability, they feel hard, lack soft tactile comfort, and may easily cause creases or aging after long use, affecting the aesthetics and use effect.
The combination of modified polyurethane materials, silicone modifiers, antistatic fillers, light stabilizers and flexible plasticizers is used to improve the softness, waterproofness, antistaticity and durability of the material through reasonable proportions and synergistic effects.
It realizes the high elasticity, waterproofness, anti-static and durability of the tablecloth, while maintaining the soft skin-feeling and touching effect, extending the service life of the product.
Smart Images

Figure CN119144144B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a highly elastic and waterproof skin-feeling tablecloth based on a flexible polymer and a preparation method thereof. Background Art
[0002] As people's pursuit of quality of life continues to improve, the comfort and versatility of household items have become important design goals. As one of the commonly used household products in daily life, the material and performance of tablecloths are constantly evolving. Traditional tablecloth materials such as natural fibers such as cotton and linen have long been popular in the market due to their soft touch and good water absorption. However, natural fiber materials are easily eroded by moisture and stains during cleaning and use, and their durability is poor, making it difficult to meet long-term wear resistance requirements. Synthetic materials such as PVC, PE, PP, etc. have gradually become the mainstream of tablecloth production, and have been recognized by the market for their good waterproofness and durability. However, these synthetic materials often feel hard, lack soft tactile comfort, and are prone to creases or aging after long use, further affecting the appearance and use effect. In order to improve the comfort and functionality of the product, in recent years, flexible polymer materials have been gradually applied to the production of tablecloths, such as polyurethane (PU) materials, which not only have high elasticity and soft feel, but also have certain wear resistance and waterproofness, becoming a new choice for improving the comfort and durability of tablecloths.
[0003] A Chinese patent (CN116394621B) discloses a waterproof and oil-proof PU printed embossed tablecloth. The polyurethane (PU) material in the patent has a certain degree of softness, but as the surface layer of the tablecloth, the modified polyurethane often increases the surface density in order to improve the waterproof and oil-proof properties, making its hydrophobic and oil-resistant properties more obvious, resulting in a relatively smooth surface and lack of soft skin-friendly touch. In addition, nylon fibers and bis-aminopropyl polydimethylsiloxane and other ingredients are added to the modified polyurethane. Although the addition of these ingredients improves the strength and durability of the material, it also increases the hardness of the material, making the overall feel hard and affecting the comfort of touch. Based on these deficiencies in the prior art, how to improve the waterproofness and elasticity of the tablecloth while maintaining its soft skin feel has become a key challenge in the industry. Summary of the invention
[0004] In the prior art, polyurethane (PU) materials have a certain degree of softness, but as the surface layer of tablecloths, modified polyurethane often increases the surface density to improve its waterproof and oil-proof properties, making its hydrophobic and oil-resistant properties more obvious, resulting in a relatively smooth surface and lack of skin-friendly soft touch. In addition, nylon fibers and bis-aminopropyl polydimethylsiloxane are added to the modified polyurethane. Although the addition of these ingredients improves the strength and durability of the material, it also increases the hardness of the material, making the overall feel hard and affecting the comfort of touch.
[0005] The present application provides a highly elastic, waterproof, skin-feeling tablecloth based on a flexible polymer. The polymer material for the tablecloth comprises: 40 to 60 parts of a modified polyurethane material, 10 to 20 parts of a siloxane modifier, 1 to 5 parts of an antistatic filler, 0.5 to 2 parts of a light stabilizer, and 5 to 15 parts of a flexible plasticizer.
[0006] As a preferred technical solution for a highly elastic and waterproof skin-feel tablecloth based on a flexible polymer, the polyurethane composition comprises: 45 parts of a modified polyurethane material, 10 parts of a siloxane modifier, 3 parts of an antistatic filler, 1 part of a light stabilizer and 10 parts of a flexible plasticizer.
[0007] It should be noted that the modified polyurethane material provides the basic mechanical properties and elasticity of the material, is the main component of the polyurethane matrix, and gives the material good flexibility and strength. The siloxane modifier effectively improves the softness and skin-feeling touch effect of the material, while improving the dispersibility and compatibility of other components in the matrix. Antistatic fillers enhance the antistatic properties of the material. Light stabilizers extend the stability of the material under ultraviolet light, prevent aging and photodegradation, and make it suitable for long-term use. Flexible plasticizers further enhance the softness and ductility of the material, improve the touch and reduce the elastic modulus, and meet the application requirements with high flexibility requirements. Through the reasonable ratio and synergistic effect of the above ingredients, the polyurethane composition has excellent mechanical properties, waterproofness, antistatic properties and durability.
[0008] As a preferred technical solution for a highly elastic and waterproof skin-feel tablecloth based on a flexible polymer, the silicone modifier is aminosilicone.
[0009] It should be noted that aminosilicone has a unique flexible chain segment structure, which can effectively reduce the rigid interaction between molecular chains after combining with the polyurethane matrix, making the material softer while maintaining strength. The flexible molecular chain of aminosilicone helps to reduce the elastic modulus of the material, improve the feel of the material, and make it more suitable for applications that require a comfortable touch. In addition, the long chain structure of aminosilicone produces a steric hindrance effect in the material, helping other additives (such as antistatic fillers and light stabilizers) to form a more uniform distribution in the material, avoiding phase separation or aggregation, thereby relatively improving the corresponding performance.
[0010] As a preferred technical solution for a highly elastic and waterproof skin-feel tablecloth based on a flexible polymer, the antistatic filler is graphene.
[0011] It should be noted that graphene, as an antistatic filler, forms an effective conductive network in the polymer matrix by relying on its high conductivity and layered structure, significantly reducing the surface resistance of the composite material, allowing static charges to move and dissipate quickly, and achieving excellent antistatic effects. The dispersion of graphene in polyurethane is a technical problem. Graphene has an extremely high specific surface area and strong π-π interaction, which makes it easy for the sheets to have van der Waals forces, thereby attracting each other and agglomerating to form an irreversible bulk structure. This agglomeration makes it difficult for graphene to be evenly dispersed in the matrix, limiting its conductivity and enhancement effect. Aminosiloxane contains "amino groups (-NH2) and siloxy groups (Si-O)". Amino groups can interact with the graphene surface through hydrogen bonds or π-π interactions, thereby helping aminosiloxane to adsorb or bond to the graphene surface. Siloxy groups can further form stable connections in the polyurethane matrix, making graphene easier to disperse evenly, thereby reducing the agglomeration of graphene sheets. Good dispersibility helps graphene form a uniform conductive network in the polyurethane matrix, thereby improving the antistatic properties of the material.
[0012] As a preferred technical solution for a highly elastic, waterproof, skin-feeling tablecloth based on a flexible polymer, the light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0013] It should be noted that the light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, which plays a key role in resisting light aging in polyurethane materials. The light stabilizer belongs to the hindered amine light stabilizer (HALS), and its unique structure enables it to effectively capture free radicals generated under light, thereby inhibiting the photooxidative degradation of polymer chains. This free radical capture mechanism helps delay the aging process of the material under ultraviolet irradiation, reduces yellowing and embrittlement, and maintains the appearance and performance of the material. In addition, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate has excellent thermal stability, can maintain structural stability under high-temperature processing and long-term ultraviolet irradiation, and is not easy to decompose or fail, thereby extending the service life of the polyurethane material.
[0014] As a preferred technical solution for a highly elastic and waterproof skin-feel tablecloth based on a flexible polymer, the flexible plasticizer is diisononyl phthalate.
[0015] It should be noted that the flexible plasticizer diisononyl phthalate (DINP) plays a significant role in improving the flexibility and ductility of the polyurethane composition. As a highly efficient plasticizer, diisononyl phthalate can penetrate into the polymer chains, reduce the interaction between molecules, and enable the polyurethane molecular chains to move more freely, giving the material higher flexibility and lower elastic modulus. This effect not only improves the softness of the material, giving it a good touch when touched, but also makes the material less likely to crack or be damaged under repeated stretching or bending, thereby improving the durability of the material.
[0016] In addition, the present invention provides a method for preparing a highly elastic and waterproof skin-feeling tablecloth, comprising the following steps:
[0017] Add the modified polyurethane material to the reactor, heat it at 60°C to 80°C in advance to ensure the fluidity of the material, then add aminosiloxane to the reactor and stir for 30 minutes, finally, add graphene to the reactor and disperse it with a high-speed stirrer, then add diisononyl phthalate and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate to the reactor in sequence;
[0018] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 80°C to 100°C, the pressure is 20 to 30 MPa, and the speed is 1 to 3 m / min.
[0019] It should be noted that the modified polyurethane material is first added to the reactor and heated at a temperature of 60°C to 80°C to ensure that the material has good fluidity. Aminosiloxane is then added to the reactor and stirred for 30 minutes to ensure that the aminosiloxane is fully mixed with the polyurethane material and enhance the dispersion effect. Next, graphene is added under high-speed stirring conditions to disperse the graphene and improve its uniformity in the matrix. Finally, the flexible plasticizer diisononyl phthalate and the light stabilizer bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate are added in sequence to ensure that the additives are evenly distributed in the composition.
[0020] The uniformly mixed polyurethane composition is poured into a calender, and the material is gradually calendered to a thickness of 0.5 to 1 mm by the calender. The temperature during the calendering process is controlled at 80°C to 100°C, the pressure is maintained at 20 to 30 MPa, and the calendering speed is set to 1 to 3 m / min to ensure the density and thickness uniformity of the material. After the material reaches the required thickness, it is cooled at room temperature and the calendered material is rolled up for use to ensure that the material has good skin feel, elasticity and waterproof properties.
[0021] As a preferred technical solution for the preparation of a highly elastic and waterproof skin-feel tablecloth, the preparation method of the modified polyurethane material includes: adding polyester polyol to a reaction kettle, preheating to 60°C, keeping stirring, and vacuum degassing under nitrogen protection to remove moisture, adding an appropriate amount of dibenzoyl disulfide to the reaction kettle and reacting for 30 minutes to 1 hour, and then adding trimer isocyanate to the reaction kettle and reacting for 30 minutes to 1 hour to obtain a modified polyurethane material.
[0022] It should be noted that, first, polyester polyol is added to the reactor, preheated to 60°C, and kept stirring. To ensure the purity of the reaction environment and prevent oxidation, the entire process is carried out under nitrogen protection, and the moisture in the system is removed by vacuum degassing to avoid moisture interference with subsequent reactions. Subsequently, an appropriate amount of dibenzoyl disulfide is added to the reactor and the reaction is continued for 30 minutes to 1 hour. The introduction of dibenzoyl disulfide helps to form disulfide bonds in the polyurethane molecular chain and enhances the degradability of the material.
[0023] Next, add trimer isocyanate to the reactor and react again for 30 minutes to 1 hour. The addition of trimer isocyanate causes the polyester polyol to polymerize with the isocyanate to form a polyurethane with a three-dimensional network structure. This process further improves the mechanical strength and stability of the material, and ultimately obtains a modified polyurethane material.
[0024] As a preferred technical solution for a method for preparing a highly elastic and waterproof skin-feeling tablecloth, the molecular weight of the polyester polyol is 1500 to 2000.
[0025] It should be noted that within the molecular weight range of 1500 to 2000, the length of the polyester polyol chain segment is moderate, neither too tight nor too loose, so that the material structure has good permeability and moderate flexibility. In this way, external degradation factors (such as water, enzymes, and microorganisms) can effectively penetrate into the interior of the material and fully contact the decomposition sites (such as ester bonds, amino groups, and sulfide bonds), thereby promoting the degradation process.
[0026] The present application provides a highly elastic waterproof skin-feel tablecloth based on a flexible polymer and a preparation method thereof, which has the following beneficial effects:
[0027] The present application significantly reduces the elastic modulus of the material by adding aminosilicone to the polyurethane composition, improves the softness and skin-friendly touch of the tablecloth, and provides users with a comfortable use experience. The design of the polyurethane matrix gives the tablecloth excellent waterproof performance, which can effectively meet the needs of waterproofing and anti-fouling in daily life and extend the service life of the product. At the same time, graphene, as an antistatic filler, forms a uniform conductive network in the material, significantly reduces the surface resistance, prevents the accumulation of static electricity, and improves the safety and practicality of the product.
[0028] In order to enhance the weather resistance of the material, hindered amine light stabilizers are added to effectively inhibit the photo-oxidative degradation caused by ultraviolet rays, prevent material aging and fading, and ensure the stability of the product in long-term use. The introduction of dibenzoyl disulfide to form a disulfide bond provides a potential biodegradation site for the material, so that the tablecloth has a certain degree of degradability, which meets the requirements of environmental protection and sustainable development. The preparation method of the present application is simple to operate, easy to industrialize, has mild process conditions, strong controllability, and reduces production costs. Combining the above advantages, the tablecloth product of the present application has excellent waterproof, antistatic and weather resistance while maintaining high elasticity and soft touch, overcoming the defects of the prior art of hard feel, insufficient waterproofness and elasticity, and has significant practical value and broad market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0030] Figure 1 This is an electron microscope image of the modified polyurethane material for tablecloth prepared in Example 1;
[0031] Figure 2 This is the experimental data diagram of Example 5. DETAILED DESCRIPTION
[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0033] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0034] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0035] Preparation Example 1
[0036] The preparation method of the modified polyurethane material comprises:
[0037] Add polyester polyol with a molecular weight of 500 into the reactor, preheat to 60°C, keep stirring, and vacuum degas under nitrogen protection to remove moisture. Add an appropriate amount of dibenzoyl disulfide into the reactor and react for 1 hour. The mass ratio of dibenzoyl disulfide to polyester polyol is 2wt%. Then add trimer isocyanate into the reactor and react for 1 hour to obtain a modified polyurethane material.
[0038] Preparation Examples 2 to 6 differ from Preparation Example 1 in the molecular weight of the polyester polyol, as shown in Table 1 below.
[0039] Table 1 Molecular weight of polyester polyols of Preparation Examples 1 to 6
[0040]
[0041] Preparation Example 7
[0042] The preparation method of the polyurethane material comprises:
[0043] Add polyester polyol with a molecular weight of 1500 into the reactor, preheat to 60°C, keep stirring, and vacuum degas under nitrogen protection to remove moisture. Add trimer isocyanate into the reactor and react for 1 hour to obtain a modified polyurethane material.
[0044] Example 1
[0045] Example 1 provides a highly elastic waterproof skin-feeling tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0046] The polymer material for tablecloth includes: 40 parts of modified polyurethane material (Preparation Example 3), 15 parts of aminosiloxane, 1 part of graphene, 2 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and 10 parts of diisononyl phthalate.
[0047] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0048] 40 parts of modified polyurethane material were added to the reactor, which was preheated at 80°C to ensure the fluidity of the material. 15 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 1 part of graphene was added to the reactor and dispersed using a high-speed stirrer. 10 parts of diisononyl phthalate and 2 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence.
[0049] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 100°C, the pressure is 20 MPa, and the speed is 2 m / min.
[0050] Example 2
[0051] Example 2 provides a highly elastic waterproof skin-feel tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0052] The polymer material for tablecloth includes: 45 parts of modified polyurethane material (Preparation Example 3), 10 parts of aminosiloxane, 3 parts of graphene, 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate and 10 parts of diisononyl phthalate.
[0053] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0054] 45 parts of modified polyurethane material were added to the reactor, which was preheated at 60°C to ensure the fluidity of the material. Then 10 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 3 parts of graphene were added to the reactor and dispersed using a high-speed stirrer. Then 10 parts of diisononyl phthalate and 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence.
[0055] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 80°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0056] Example 3
[0057] Example 3 provides a highly elastic waterproof skin-feel tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0058] The polymer material for tablecloth includes: 60 parts of modified polyurethane material (Preparation Example 3), 20 parts of aminosiloxane, 1 part of graphene, 0.5 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and 15 parts of diisononyl phthalate.
[0059] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0060] 60 parts of modified polyurethane material were added to the reactor, which was preheated at 70°C to ensure the fluidity of the material. 20 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 1 part of graphene was added to the reactor and dispersed using a high-speed stirrer. 15 parts of diisononyl phthalate and 0.5 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence.
[0061] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 90°C, the pressure is 30 MPa, and the speed is 1 m / min.
[0062] Example 4
[0063] Example 4 provides a highly elastic waterproof skin-feeling tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0064] The polymer material for tablecloth includes: 50 parts of modified polyurethane material (Preparation Example 3), 10 parts of aminosiloxane, 5 parts of graphene, 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and 5 parts of diisononyl phthalate.
[0065] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0066] 50 parts of modified polyurethane material were added to the reactor, which was preheated at 80°C to ensure the fluidity of the material. Then 10 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 5 parts of graphene were added to the reactor and dispersed using a high-speed stirrer. Then, 5 parts of diisononyl phthalate and 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence.
[0067] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 80°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0068] Example 5
[0069] Example 5 provides a highly elastic waterproof skin-feel tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0070] The polymer material for tablecloth includes: 50 parts of modified polyurethane material (Preparation Example 1, Preparation Example 2, Preparation Example 3, Preparation Example 4, Preparation Example 5, Preparation Example 6), 15 parts of aminosiloxane, 4 parts of graphene, 1.5 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate and 5 parts of diisononyl phthalate.
[0071] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0072] 50 parts of modified polyurethane material were added to the reactor, which was preheated at 70°C to ensure the fluidity of the material. 15 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 4 parts of graphene were added to the reactor and dispersed using a high-speed stirrer. 5 parts of diisononyl phthalate and 1.5 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence.
[0073] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 100°C, the pressure is 25 MPa, and the speed is 3 m / min.
[0074] Comparative Example 1
[0075] Comparative Example 1 provides a highly elastic waterproof skin-feeling tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0076] The polymer material for tablecloth includes: 55 parts of modified polyurethane material (Preparation Example 3), 3 parts of graphene, 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and 10 parts of diisononyl phthalate.
[0077] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0078] 55 parts of modified polyurethane material were added to the reactor, which was preheated at 80°C to ensure the fluidity of the material. 3 parts of graphene were added to the reactor and dispersed using a high-speed stirrer. Then 10 parts of diisononyl phthalate and 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence.
[0079] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 80°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0080] Comparative Example 2
[0081] Comparative Example 2 provides a highly elastic waterproof skin-feeling tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0082] The polymer material for tablecloth includes: 45 parts of polyurethane material (Preparation Example 7), 10 parts of aminosiloxane, 3 parts of graphene, 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate and 10 parts of diisononyl phthalate.
[0083] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0084] 45 parts of modified polyurethane material were added to the reactor, which was preheated at 60°C to ensure the fluidity of the material. Then 10 parts of aminosiloxane were added to the reactor and stirred for 30 minutes. Finally, 3 parts of graphene were added to the reactor and dispersed using a high-speed stirrer. Then 10 parts of diisononyl phthalate and 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence.
[0085] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 80°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0086] Comparative Example 3
[0087] Comparative Example 3 provides a highly elastic waterproof skin-feeling tablecloth based on a flexible polymer and a preparation method thereof, wherein:
[0088] The polymer material for tablecloth includes: 48 parts of modified polyurethane material (Preparation Example 3), 10 parts of aminosiloxane, 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and 10 parts of diisononyl phthalate.
[0089] The preparation method of the highly elastic waterproof skin-feeling tablecloth comprises the following steps:
[0090] 45 parts of modified polyurethane material were added to the reactor, which was preheated at 60°C to ensure the fluidity of the material, and then 10 parts of aminosiloxane were added to the reactor, stirred for 30 minutes, and then 10 parts of diisononyl phthalate and 1 part of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate were added to the reactor in sequence;
[0091] Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 80°C, the pressure is 30 MPa, and the speed is 3 m / min.
[0092] Table 2 shows the composition ratios of the polyurethane compositions of Examples 1 to 5 and Comparative Examples 1 to 3.
[0093]
[0094] Performance testing
[0095] 1. According to GB / T 12703.2-2009 standard, use an electrostatic voltage tester to measure the surface resistance or electrostatic decay time of the material;
[0096] 2. Refer to GB / T 4745-2012 standard and use a water contact angle tester to test the contact angle of water droplets on the tablecloth surface;
[0097] 3. Use a tensile tester to test the elastic modulus of the material. The lower the elastic modulus, the softer the material and the better the touch.
[0098] 4. The simulated soil degradation test is used to evaluate the biodegradability of materials in a soil environment. First, cut the material sample into small pieces of 10x10 mm and accurately weigh the initial mass. Use active natural soil or standard soil to ensure a water content of 40% to 60% and a pH value of 6.0-8.0 to maintain microbial activity. Place the soil and sample in a breathable container, bury the sample at a depth of about 2-3 cm, and prepare biodegradable materials such as cellulose as a control. The test environment is controlled within the range of 20-30°C and placed in a constant temperature and humidity chamber away from direct sunlight. Take out the sample after 60 days, remove the surface attachments, weigh the remaining mass, and calculate the degradation rate.
[0099] Table 3 Experimental data of Examples 1 to 4 and Comparative Examples 1 to 3
[0100]
[0101] Combined with Example 1 and Figure 1 It can be seen that the polyurethane material prepared by the formula and process of the present application exhibits uniformity in microstructure, and the added graphene is well dispersed in the polyurethane matrix, thereby avoiding the non-uniformity of material properties. This dispersion effect is mainly due to the use of modifiers such as aminosiloxane in the formula, which improve the interface compatibility between the filler and the polyurethane matrix, so that the filler can be evenly distributed in the matrix without agglomeration.
[0102] Combining Examples 1 to 4 and Table 3, it can be seen that the water contact angle, elastic modulus, mass loss rate and surface resistance of Examples 1 to 4 are 115°-130°, 28.5-30.2 MPa, 18%-25% and 10 8 Ω-10 10Ω, the polymer material for tablecloth prepared by the formula and preparation process of the present application shows excellent waterproofness, softness, degradability and antistatic properties.
[0103] Combining Example 2, Control Example 1 and Table 3, it can be seen that the aminosilicone component is removed in Control Example 1, and the various properties in Control Example 1 are worse than those in Example 2. This is mainly because aminosilicone has a unique flexible segment structure, which can effectively reduce the rigid force between molecular chains after combining with the polyurethane matrix, making the material softer while maintaining strength. The flexible molecular chain of aminosilicone helps to reduce the elastic modulus of the material and improve the feel of the material, making it more suitable for applications requiring comfortable touch. In addition, the long chain structure of aminosilicone produces a steric hindrance effect in the material, helping other additives (such as antistatic fillers, light stabilizers) to be more evenly distributed in the material, avoiding phase separation or aggregation, thereby relatively improving various properties.
[0104] Combining Example 2, Control Example 2 and Table 3, it can be seen that the mass loss rate of Control Example 2 is significantly lower than that of Example 2, mainly because in the biodegradation process, the introduction of disulfide bonds (-SS-) provides a key site for microorganisms to degrade polyurethane materials. Disulfide bonds have high chemical activity and are easily attacked by microbial enzymes. The enzymes secreted by many microorganisms (such as bacteria and fungi) can recognize and degrade sulfur-containing compounds, thereby breaking the disulfide bonds. In this process, the disulfide bonds are broken down into sulfhydryls (-SH) or small molecular sulfur-containing compounds, which are further converted into substances that can be metabolized by microorganisms (such as sulfates or other inorganic salts), and are eventually completely decomposed by microorganisms. With the breaking of the disulfide bonds, the polyurethane molecular chains gradually disintegrate into smaller fragments, and these low molecular weight polymer fragments are more easily further decomposed and metabolized by microorganisms. Therefore, the presence of disulfide bonds not only provides an effective breaking site for the biodegradation of the material, but also degrades the material into harmless small molecules through microbial metabolism, thereby accelerating the biodegradation process of the polyurethane material in the natural environment.
[0105] Combining Example 2, Control Example 3 and Table 3, it can be seen that the antistatic performance of Control Example 3 is inferior to that of Example 2. The graphene particles have strong polarity and can form a microscopic conductive network in the polyurethane matrix, thereby increasing the mobility of charges in the material, thereby reducing static electricity accumulation and effectively improving the antistatic performance of the polyurethane composition.
[0106] Combined with Example 5 and Figure 2It can be seen that when the molecular weight of the polyester polyol is between 1500 and 2000, the degradability of the polyurethane composition reaches the best state. Outside this range, lower or higher molecular weights will lead to a more obvious decrease in degradability. This is mainly because within the molecular weight range of 1500 to 2000, the length of the polyester polyol chain segment is moderate, neither too tight nor too loose, so that the material structure has good permeability and moderate flexibility. In this way, external degradation factors (such as water, enzymes, and microorganisms) can effectively penetrate into the material and fully contact with the decomposition sites (such as ester bonds, amino groups, and sulfide bonds) to promote the degradation process. When the molecular weight is low (such as 500-1000), the material structure is too tight and the decomposition sites are difficult to expose, which hinders the penetration of degradation factors. On the contrary, when the molecular weight is high (such as 2500-3000), the long chain structure causes the material to cross-link too much, forming a denser network, which is not conducive to the diffusion of degradation factors. Therefore, the molecular weight range of 1500 to 2000 is the optimal degradation condition for the polyurethane composition.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Highly elastic waterproof skin-feel tablecloth based on flexible polymer, characterized in that: The polymer material for tablecloth comprises: 40 to 60 parts of modified polyurethane material, 10 to 20 parts of siloxane modifier, 1 to 5 parts of antistatic filler, 0.5 to 2 parts of light stabilizer and 5 to 15 parts of flexible plasticizer; The siloxane modifier is aminosiloxane; the antistatic filler is graphene; The preparation method of the modified polyurethane material comprises: Add polyester polyol into a reaction kettle, preheat to 60°C, keep stirring, and vacuum degas under nitrogen protection to remove moisture, add an appropriate amount of dibenzoyl disulfide into the reaction kettle and react for 30 minutes to 1 hour, then add trimer isocyanate into the reaction kettle and react for 30 minutes to 1 hour to obtain a modified polyurethane material; the molecular weight of the polyester polyol is 1500 to 2000.
2. The highly elastic waterproof skin-feeling tablecloth according to claim 1, characterized in that: The polymer material for tablecloth comprises: 45 parts of modified polyurethane material, 10 parts of siloxane modifier, 3 parts of antistatic filler, 1 part of light stabilizer and 10 parts of flexible plasticizer.
3. The highly elastic waterproof skin-feeling tablecloth according to claim 1, characterized in that: The light stabilizer is bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
4. The highly elastic waterproof skin-feeling tablecloth according to claim 1, characterized in that: The flexible plasticizer is diisononyl phthalate.
5. A method for preparing a highly elastic and waterproof skin-feeling tablecloth, which is used for preparing a highly elastic and waterproof skin-feeling tablecloth as claimed in any one of claims 1 to 4, characterized in that: The steps include: Add the modified polyurethane material to the reactor, heat it at 60°C to 80°C in advance, add aminosiloxane to the reactor, stir for 30 minutes, finally, add graphene to the reactor, disperse it with a high-speed stirrer, and then add diisononyl phthalate and bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate to the reactor; Pour the evenly mixed polyurethane composition into a calender, gradually calender the composition to a thickness of 0.5 mm to 1 mm, keep the material cooled at room temperature, and roll up the calendered material for use, wherein the temperature of the calender is 80°C to 100°C, the pressure is 20 to 30 MPa, and the speed is 1 to 3 m / min.
Citation Information
Patent Citations
A waterproof and oil-proof PU printed embossed tablecloth
CN116394621B
Preparation method of solvent-free polyurethane with self-repairing function and preparation method thereof
CN116217871A
Degradable self-expanding bioactive bone adhesive and application thereof
CN118121745A